Piloting the Appreciative Tuning Protocol: Improving Integration through a Collaborative Professional Development Model - Teresa S. Foulger; Ashleigh King; Shyla Gonzalez-Dogan (International Journal for the Scholarship of Teaching and Learning)
This qualitative, self-reflection study was conducted by three instructors who had recently participated in a workshop on Principled Innovation, a character development framework designed in their college of education. They were confident about how they integrated PI into their courses but saw potential for further improvement. Drawing on collaborative professional development literature, they explored two models, Appreciative Inquiry and Tuning, that seemed to meet their needs. By merging elements of both, they created the Appreciative Tuning Protocol (ATP), a 30-minute, agenda-driven meeting where instructors identify a successful part of the integration effort (a bright spot), explore ways to enhance it, and then support the course instructor in determining next steps. This study documents their pilot of the ATP. The data included video-based course tours of all three courses, the ATP meeting transcripts, and the instructors’ written reflections. Findings showed that the ATP helped the instructors maintain an asset-based orientation, ensure equal contributions, and facilitate honest communication. Importantly, the ATP met the instructors’ professional development expectations about improving PI integration in their courses in a time-efficient manner. Further research is needed to determine if the ATP is useful for other content integration efforts and for other course domains in higher education.